BROADBAND INTERNET, FIRM PERFORMANCE, AND WORKER WELFARE: EVIDENCE AND MECHANISM. (5th November 2019) - Chen, Shiyi; Liu, Wanlin; Song, Hong
Abstract : This paper examines the effect of high‐speed internet on firm's productivity and worker's wage in China. We exploit a national policy reform and devise a difference‐in‐difference strategy to address the endogeneity. We find that high‐speed internet significantly increases firm's productivity and worker's wage, and the estimate is larger for firms in industries with high skill intensity and for more educated workers. We provide suggestive evidence that the mechanism is likely from firm's increased use of skill‐biased technology and the flattened management organization. ( JEL O2, O3, J3)